Toxic effects, mechanisms, and ecological impacts of harmful algal blooms in China - Yan, Tian; Li, Xiao-Dong; Tan, Zhi-Jun; Yu, Ren-Cheng; Zou, Jing-Zhong (Harmful algae, 2022)
•HABs which caused huge financial losses or fishery impacts in China coasts were summarized.•Causative species shifting and increasing diversity of HABs were reported in this region.•HAB species showed impacts on multiple organisms of different trophic levels.•The main mechanism for toxicity appears to vary with the type of HAB species. Over the last 30 years, harmful algal blooms (HABs) have occurred frequently in the coastal waters of China, resulting in financial losses of over 5.9 billion yuan (about 0.87 billion US dollars) due to massive fish and shellfish mortalities and negative impacts on tourism. To better understand HABs in China, herein we summarized bloom events with massive fish/shellfish mortalities and/or economic losses. Our results suggest that the diversity of HAB species has increased over the last 30 years, with the main causative species shifting from the raphidophyte Chattonella marina and dinoflagellates Gymnodinium spp. to various other species, including the dinoflagellates Karenia mikimotoi and Prorocentrum donghaiense, the haptophyte Phaeocystis globosa, and the pelagophyte Aureococcus anophagefferens. In addition, new types of HABs, such as macroalgal blooms, emerged with severe ecological impacts. We also reviewed the toxic effects, mechanisms, and ecological impacts of common HAB causative species in China. Analysis of the toxic effects of three types of harmful algae (toxin-producing, fish killing, and ecosystem disruptive algae) on marine organisms commonly found in China at different trophic levels revealed that HABs often had toxic effects on multiple organisms in addition to fish or shellfish, with species-specific impacts. Common mechanisms of intoxication include shifting environmental parameters, shellfish poisoning, reactive oxygen species, and haemolytic/cytotoxic toxins. The main mechanism appears to vary with the type of HAB species, and for some notorious algae such as K. mikimotoi and C. marina, further investigations are needed to identify their intoxication mechanism.